(untitled) (Bioagro, 2020)
Current trends in agriculture involve the use of farming practices conditions aimed at improving the fruit nutritional value by directly affecting the content of antioxidants. Chile is the second-largest blueberry-producing country in the world, and the biggest exporting country in the South hemisphere. Therefore, the purpose of this study was to evaluate if production systems (organic and conventional) in two consecutive seasons and two different agro-climatic zones (Andean foothill and Central Valley) have differences in the concentration of the main polyphenol and anthocyanin compounds, and antioxidant capacity, in three blueberry cultivars (‘Brigitta’, ‘Duke’ and ‘Legacy’) grown in andisol soils. The cultivars Legacy and Duke presented the greatest content of polyphenols and the highest antioxidant capacity, as well as important antioxidant compounds. Similarly, both polyphenol contents and antioxidant capacity reached superior values in organically grown blueberries, which means that this production system represents an important aspect to take into account. These results support an expansion of organic farming as strategy for the achievement on fruits quality in this kind of soils.